Public health challenges – the diet, nutritional status, and health of the Polish population - Anna Harton (Journal of Health Inequalities)
Eating habits affect your nutritional status and overall health. Poor eating habits established early in life can lead to various health issues during childhood and later adulthood, increasing the risk of diet- related diseases at all life stages. An unhealthy lifestyle often results in excess body weight, which is becoming more common across different age groups, including young children. Obesity is one of the most pressing public health challenges today. Obesity often coexists with other diseases or can elevate the risk of developing these conditions. There is an urgent need for comprehensive, systemic solutions to improve the health of Polish society. Health education, particularly nutritional education, can enhance diet, nutritional status, and overall health. It is crucial to promote healthy lifestyle habits starting in childhood. The article discusses the diet of Poles, including unhealthy dietary choices in different age groups in relation to selected nutritional recommendations. Attention is drawn to the role of social media in promoting knowledge, awareness, and attitudes towards food and nutrition. Dietary deficiencies and their impact on nutritional status are discussed. The epidemiological situation of obesity is characterised as an example of diet-related disease. Finally, selected nutritional education programs for children and adolescents implemented in Poland in the last decade are described.